Associação conjunta entre atividade física, tempo de tela e transtorno mental comum em adolescentes brasileiros - Mendes, Túlio Chaves (2025)
Introduction: common mental disorders (CMD), such as symptoms of anxiety, depression, and somatic complaints, have been increasing, particularly among young people, impacting their health. Physical activity has been associated with a reduction in CMD, whereas excessive screen time has been linked to worsening of these symptoms. Objective: to analyze the joint association between physical activity, screen time, and CMD among Brazilian adolescents aged 12 to 17 years, considering a dose-response gradient. Methods: Data were obtained from the Study of Cardiovascular Risk Factors in Adolescents (ERICA), a multicenter crosssectional study conducted between 2013 and 2014 with adolescents from public and private schools in Brazilian municipalities with more than 100,000 inhabitants. Physical activity was assessed using a questionnaire on moderate to vigorous physical activities, and screen time was quantified through a questionnaire on daily hours spent using computers, watching television, and playing video games. The occurrence of CMD was measured by the 12-item General Health Questionnaire (GHQ-12). Poisson regression models with robust variance stratified by sex were used in the analyses. Results: a total of 65,048 adolescents were evaluated, with a mean age of 14.7 years. The prevalence of CMD was 16.9% higher among girls. Excessive screen time (≥ 6 hours/day) was positively associated with CMD in adjusted analyses, both in girls (PR: 1.60; 95% CI: 1.44–1.79) and in boys (PR: 1.40; 95% CI: 1.15–1.72). Regarding physical activity, a U-shaped association between physical activity and CMD was observed, with greater protection among boys. In the joint associations of physical activity and screen time with CMD, not engaging in physical activity (0 min/day) combined with excessive screen time (≥ 6 hours/day) resulted in prevalence ratios 46% and 72% higher among girls and boys, respectively. In the stratified analysis, an attenuation in the association between screen time and CMD was observed according to the level of physical activity among boys. Conclusion: this study observed that engaging in physical activity and limiting screen time are associated with a lower prevalence of CMD among Brazilian adolescents. Public policies aimed at promoting healthy behaviors may have an impact on adolescent mental health.